Comparison of the Effectiveness of Sports Vision Training and Conventional Methods on Functional Ability and State-Competitive Anxiety of Young Volleyball Players in a Supervised Environment - Srayyih Hammood Al-Fraidawi , Hussein; Zahedi, Hamid; Muhsun Yasir Al-uoda, Alaa; Meshkati, Zohreh (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: The present study aimed to compare the effects of three training methods—sports vision, combined, and specialized/traditional—on functional ability and components of state-competitive anxiety in young Iraqi volleyball players under supervised conditions.Methods and Materials: This research employed a semi-experimental and applied design conducted in the field using a pre-test–post-test plan. A total of 42 participants were recruited and randomly assigned to three groups (n = 14 each): sports vision, combined, and specialized/traditional. Data analysis was performed using analysis of covariance and Bonferroni post-hoc tests through SPSS version 23 at a significance level of less than .05.Findings: The findings revealed significant differences among the three training groups in both functional and psychological variables. Regarding performance indicators, although no significant differences were observed among the groups in vertical jump, the combined training group demonstrated significantly better performance than the specialized/traditional group in displacement time under supervisory pressure and evaluation conditions (p = .003). In the psychological domain, the results indicated significant differences between groups. Both the sports vision and combined training groups, compared to the specialized/traditional group, showed a significant reduction in cognitive anxiety (p = .000) and somatic anxiety (p = .000), as well as a significant increase in self-confidence (p = .000).Conclusion: These findings confirm the superiority of modern training methods (combined and sports vision training) in improving psychological indicators that influence athletic performance.